2021
DOI: 10.1021/acs.orglett.1c01419
|View full text |Cite
|
Sign up to set email alerts
|

Metal- and Base-Free C(sp2)–H Arylsulfonylation of Enamides for Synthesis of (E)-β-Amidovinyl Sulfones via the Insertion of Sulfur Dioxide

Abstract: A metal- and base-free C­(sp2)–H direct arylsulfonylation of secondary and tertiary enamides with aryldiazonium salts and ex situ generated SO2 (from SOgen) is presented. This method runs smoothly to produce β-amidovinyl sulfones with excellent stereoselectivities in moderate to excellent yields. Moreover, this strategy features good functional group tolerance and environmentally benign reaction conditions. Mechanistic experiments indicate that this sulfonylation may proceed in a radical pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The DFT studies (Fig. 9, see the ESI† for details) and subsequent literature studies 70–74 showed that aryl radicals are not readily generated in the visible-light-induced cyclization of 1,6-enynes with aryl sulfonyl groups, which was reported previously. Furthermore, owing to the difference in reactivity between the alkynes and alkenes, the alkyne π-bonds are stronger and less reactive than the alkene π-bonds.…”
Section: Resultssupporting
confidence: 64%
“…The DFT studies (Fig. 9, see the ESI† for details) and subsequent literature studies 70–74 showed that aryl radicals are not readily generated in the visible-light-induced cyclization of 1,6-enynes with aryl sulfonyl groups, which was reported previously. Furthermore, owing to the difference in reactivity between the alkynes and alkenes, the alkyne π-bonds are stronger and less reactive than the alkene π-bonds.…”
Section: Resultssupporting
confidence: 64%
“…More recently, Zhang and Lian further established a transition-metaland base-free strategy for the arylsulfonylation of enamides by using a cheap and bench-stable SO 2 surrogate (tetrabromothiophene S,S-dioxide, SOgen), 525 which could ex situ generate SO 2 gas in a controlled and predictable manner (Scheme 325c). 526 5.1.8. Phosphorylation.…”
Section: Olefinationmentioning
confidence: 99%
“…This process occurred under benign conditions, giving rise to the corresponding β-amidovinyl sulfones in up to 91% yield. More recently, Zhang and Lian further established a transition-metal- and base-free strategy for the arylsulfonylation of enamides by using a cheap and bench-stable SO 2 surrogate (tetrabromothiophene S , S -dioxide, SOgen), which could ex situ generate SO 2 gas in a controlled and predictable manner (Scheme c) …”
Section: Alkenyl C–h Bond Functionalization Of Alkenes Containing a H...mentioning
confidence: 99%
“…In this regard, Willis and Jiang’s groups, respectively, developed efficient palladium-catalyzed sulfone synthesis reactions by using DABCO·(SO 2 ) 2 and thiourea dioxide instead of SO 2 gas . Recently, the groups of Jiang, Wu, and others disclosed a number of elegant radical-medicated sulfonylation reactions by using DABCO·(SO 2 ) 2 , Na 2 S 2 O 5 , thiourea dioxide, Na 2 S 2 O 4 , and SOgen (tetrabromothiophene S , S -dioxide) as the SO 2 source . Compared with the insertion of an extra SO 2 strategy, the capture of SO 2 generated in situ from substrate is undoubtedly atom-economical and environmentally friendly but more challenging (Scheme , c) because the released SO 2 is generally at low concentrations and difficult to capture by low-lived, high-activity radicals.…”
mentioning
confidence: 99%